2007
DOI: 10.1177/1545109707302088
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Population-Based Study of Knowledge, Attitudes, and Practices Regarding HIV/AIDS in Dakshina Kannada District of Karnataka, India

Abstract: HIV/AIDS prevention campaigns in India should focus on public education, stigma reduction, promotion of condom use, and risk-reduction behaviors in urban and rural communities targeted toward young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 20 publications
4
20
0
Order By: Relevance
“…Our findings are consistent with other studies where casual contact, mosquito bite, bed bugs, public toilets, pools, and sharing meals have been considered as modes of HIV transmission by the participants [6, 14, 16–18]. As with other studies misconceptions were more among the respondents who were nonliterate [14, 19, 20].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with other studies where casual contact, mosquito bite, bed bugs, public toilets, pools, and sharing meals have been considered as modes of HIV transmission by the participants [6, 14, 16–18]. As with other studies misconceptions were more among the respondents who were nonliterate [14, 19, 20].…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrates that despite of high awareness regarding disease among rural people more than thirty percent of people had unfavorable attitude towards the disease. Study done by Meundi et al [12] also shows the similar finding.…”
Section: Discussionsupporting
confidence: 77%
“…[11] It was surprisingly evident that only 35.5% of students had received HIV prevention education during their curriculum and only 22.3% of the students knew about Integrated counseling and testing centers. A previous study in India has shown that intervention programs providing such education in the schools have resulted in marked improvement in knowledge and were associated with more positive attitude of students towards the disease.…”
Section: Discussionmentioning
confidence: 99%